Porous equipotential body with heterogeneous nucleation sites: A novel 3D composite current collector for lithium metal anode. (20th June 2019) - Jia, Weishang; Chen, Tao; Wang, Ying; Qu, Siji; Yao, Zeyu; Liu, Yuchi; Yin, You; Zou, Wei; Zhou, Fu; Li, Jingze
Abstract: Lithium metal is an ideal anode material for lithium battery thanks to its ultra-high specific capacity and lowest redox potential. However, uncontrollable growth of lithium dendrites hinders its application due to local aggregation of lithium ions and anisotropic growth of lithium metal driven by uneven electric field distribution. Here a strategy is proposed to address this issue via utilizing porous equipotential body decorated with heterogeneous nucleation sites as advanced three-dimensional current collector. The conductive network of carbon nanofibers is recognized as a porous equipotential body, where the interior electric filed is zero due to the well-defined electric field shielding effect. In addition, copper nanoparticles as heterogeneous nucleation sites are uniformly anchored on carbon nanofibers, which guide lithium deposition evenly. As a result, lower impedance and higher Coulombic efficiency (∼97%) are achieved in modified lithium-copper cell. In particular, the cycling lifetime of modified symmetric lithium-lithium cell is expanded up to 500 cycles at extremely large current density of 50 mA cm −2 .